The influence of online-based hypnoteaching methods on the biology learning outcomes of class xi students - May Yarni; Berliana Cakra Kusuma (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
This study aims to improve student learning outcomes by applying Online-Based Hypnoteaching Learning Methods. The method used is quasi-experimental. The sample consisted of 69 students selected randomly. Data collection uses pretest and post-test with learning outcomes test instruments. The experimental class n-gain test has an index score of 59.1%, which means relatively effective, while the control class has an index score of 31.0%, which means ineffective. The result of learning outcomes proves significant differences between the two categories. Student responses using the models strongly agree between 49.12% and 43.00%. The assumption test shows that the data were normally distributed and homogeneous. The hypothesis test is obtained Tcount (4.46) Ttable (1.99), indicating the influence of the application online-based hypnoteaching learning model in improving the learning outcomes of student classes in 11th-grade science classes.